The coronavirus disease 2019 and effect on liver function: a hidden and vital interaction beyond the respiratory system. Issue 1 (18th January 2022) - Hosseini, Parastoo; Afzali, Shervin; Karimi, Mohammadreza; Zandi, Milad; Zebardast, Arghavan; Latifi, Tayebe; Tabibzadeh, Alireza; Ramezani, Akam; Zakeri, Armin; Zakeri, Amirmohammad; Abedi, Behnam; Soltani, Saber; et al.
Abstract : Severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) emerged in December 2019 in Wuhan province, China. SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). Angiotensin-converting enzyme 2 (ACE2) has an essential role as a receptor in the entry of the SARS-CoV-2 into the host cells. It has been declared, ACE2 expresses in the lungs, heart, kidneys, placenta, and liver. This study reviews the liver's markers' characteristics in patients with COVID-19 to achieve novel insights in improving clinical treatment. Liver disease and chronic kidney disease patients are susceptible to COVID-19. There is limited information about the effects of SARS-COV-2 on patients with preexisting liver associated disorders, including chronic hepatitis B virus or hepatitis C virus, primary biliary cirrhosis, nonalcoholic fatty liver disease, and more are yet to be understood. By considering conducted studies in this manner since ACE2 receptors, which are the primary receptors for SRAS-CoV-2, exist on the liver and lungs, heart, kidneys, and placenta, SRAS-CoV-2 can infect liver cells too. Consequently, this infection will have resulted in liver function tests' escalated levels and total bilirubin as biochemical biomarkers. Further investigations need to be done to point out the hepatic manifestations of COVID-19's infected patients with chronic liver disease and improve clinical management and more stringent preventive measures for this type of infected patients.